INISIASI PEMBELAJARAN MATEMATIKA DENGAN ETNOMATEMATIKA DAN TEORI BELAJAR BRUNER - Nursantoso, Aryadi (AL-QALAM: JURNAL KEPENDIDIKAN, 2023)
Mathematics can be considered a difficult subject by some people because it requires the ability to think abstractly. The power of abstraction in mathematics refers to a person's ability to think conceptually and generalize patterns found in a mathematical context. The purpose of this research is to initiate the development of mathematics learning using ethnomathematics and Bruner's theory of learning, aiming to facilitate students in mastering mathematical concepts that require high abstraction. This research employs a literature review method and utilizes discourse analysis as the data analysis technique. Ethnomathematics involves utilizing and integrating cultural practices and mathematics within society to enhance students' understanding of mathematical concepts. This approach is integrated with Bruner's learning theory by incorporating cultural elements into the stages of enactment, iconic representation, and symbolic representation. By combining these two theories, a deeper understanding of mathematics is expected, connecting the learned theories with students' cultural backgrounds and experiences. Thus, mathematics learning is anticipated to become more meaningful and relevant to the realities faced by students in their daily lives.